Achieving reliable and secure services in cloud computing environments. (April 2017) - Liu, Qin; Wang, Guojun; Liu, Xuhui; Peng, Tao; Wu, Jie
Highlights: We propose a Comprehensive Transmission (CT) model by combining the C/S mode and the P2P mode for data transmission. The CT model makes full use of the advantages of the C/S mode and the P2P mode for reliable data transmission in cloud computing environments. We design a Two-Phase Resource Sharing (TPRS) protocol, which mainly consists of a pre-filtering phase and a verification phase. The TPRS protocol utilizes the techniques of Secure Dot-Product (SDP) protocol, the Fuzzy Vault (FV) and Attribute-Based Encryption (ABE) to efficiently and privately achieve authorized resource sharing in cloud computing environments. Graphical abstract: Abstract: In cloud computing environments, resources stored on the cloud servers are transmitted in the form of data flow to the clients via networks. Due to the real-time and ubiquitous requirements of cloud computing services, how to design a sophisticated transmission model to ensure service reliability and security becomes a key problem. In this paper, we first propose a Comprehensive Transmission (CT) model, by combining the Client/Server (C/S) mode and the Peer-to-Peer (P2P) mode for reliable data transmission. Then, we design a Two-Phase Resource Sharing (TPRS) protocol, which mainly consists of a pre-filtering phase and a verification phase, to efficiently and privately achieve authorized resource sharing in the CT model. Extensive experiments have been conducted on the synthetic data set to verify the feasibility of our protocol.